P145. Transcranial biphasic quadro-pulse stimulation with one but not two full-sine cycles induces long-term depression-like corticomotor plasticity. Issue 8 (August 2015) - Jung, N.H.; Gleich, B.; Kalb, A.; Limburg, K.; Gattinger, N.; Fritsch, J.; Siebner, H.R.; Mall, V.
<x xml:space="preserve">Abstract</x> Question Neuronal plasticity in form of long-term potentiation (LTP) and long-term depression (LTD) is considered to be the neurophysiological mechanism of learning and memory. There is growing evidence that the induction of LTD-like effects plays a crucial role in mediating therapeutic effects of transcranial magnetic stimulation (TMS). We previously demonstrated that biphasic transcranial quadro-pulse stimulation (QPS) consisting of two-full sine cycles is slightly more effective than with one full-sine cycle in induction of LTP-like effects in human primary motor cortex. Here, we aimed to study the effectiveness of QPS with one and two full-sine cycles in induction of LTD-like effects of synaptic plasticity. Methods We investigated healthy volunteers (n = 7 per protocol) with quadro-pulse stimulation consisting of one (QPS-1) and two (QPS-2) full-sine cycles (duration: 160 μs, respectively) separated by an inter-stimulus interval of 50 ms and an inter-burst interval of 200 ms with a total amount of 1440 pulses. Resting motor threshold (rMT), and motor evoked potential (MEP) amplitudes with stimulus intensities to target amplitudes of 1 mV (SI1mV) were measured before (Pre) intervention, directly after (Post1), after 15 min (Post2), after 30 min (Post3) and after 60 min (Post4). Results We found a significant decrease of MEP amplitudes after QPS-1 but not after QPS-2 at all time points lasting for 1 h (Post 1–4). No significant changes in rMT were observed. Conclusion QPS with one full-sine-cycle induces LTD-like changes in human primary motor cortex at interstimulus intervals of 50 ms. Using two-full sine cycles – previously demonstrating to be more effective in induction of LTP-like plasticity at interstimulus intervals of 5 ms – did not lead to changes in corticomotor excitability. These divergence in the capability to induce corticomotor plasticity suggests different underlying neurophysiological mechanisms. The results may be of interest when applying QPS or other patterned stimulation protocols therapeutically.